(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The phosphoprotein P is multifunctional and the less conserved among Rabies virus (RABV) proteins, associated with the ribonucleoprotein (RNP), with a role in the binding of the polymerase L in the RNP. Interactions involving P are related to RABV tropism, the cell-to-cell virus spread and inhibition of innate immune response that interferes with or stops the replication of viruses. P is also involved in the trans-axonal transport of RABV and interferon (IFN) inhibition, which could modulate the pathogenesis viral. There are hypotheses that the RABV proteins polymorphisms can lead to variations in the replication efficiency of different strains of RABV in different hosts, culminating in variable viral titers, modulating viral pathogenesis and leading to different efficiencies of intra-axonal transport and function as a co-factor in the synthesis of viral RNA. However there is still much to be clarified on this subject. To this end, 29 RABV strains from bats of the genus Artibeus sp. isolated in mouse brain were selected with variable lethality (LET) and incubation periods (IP) in days after inoculation in the central nervous system of mice. The samples were subjected to titration in N2a cell cultures and complete sequencing of the P gene. Data analysis including LET, IP and titer in association with the pattern of segregation of the viral strains studied in the phylogenetic tree showed no association between these variables and polymorphisms of the P Gene. It can be speculated that other proteins, such as the polymerase L, currently under consideration by the authors, may have an important role in the modulation of incubation and lethality, when considering viral strains that are very closely related regarding the P gene. This information is applicable for discussions about the importance of rabies reservoirs, the dynamic of the virus and the different forms of host-virus co-evolution, contributing to further studies on RABV pathogenesis.